The acid invertase gene family is involved in internode elongation in Phyllostachys heterocycla cv. pubescens. (25th April 2020) - Guo, Xiaoqin; Chen, Hongjun; Liu, Yue; Chen, Wei; Ying, Yeqing; Han, Junjie; Gui, Renyi; Zhang, Hongxia
Abstract: Acid invertases (INVs) play a pivotal role in both vegetative and reproductive growth of plants. However, their possible functions in fast-growing plants such as bamboo are largely unknown. Here, we report the molecular characterization of acid INVs in Phyllostachys heterocycla cv . pubescens, a fast-growing bamboo species commercially grown worldwide . Nine acid INVs (PhINVs), including seven cell wall INVs (PhCWINV1, PhCWINV2, PhCWINV3, PhCWINV4, PhCWINV5, PhCWINV6 and PhCWINV7) and two vacuolar INVs (PhVINV11 and PhVINV12) were isolated. Bioinformatic analyses demonstrated that they all share high amino acid identity with other INVs from different plant species and contain the motifs typically conserved in acid INV. Enzyme activity assays revealed a significantly higher INV activity in the fast-growing tissues, such as the elongating internodes of stems. Detailed quantitative reverse-transcription PCR analyses showed various expression patterns of PhINVs at different developmental stages of the elongating stems. With the exception of PhCWINV6, all PhINVs were ubiquitously expressed in a developmental-specific manner. Further studies in Arabidopsis exhibited that constitutive expression of PhCWINV1, PhCWINV4 or PhCWINV7 increased the biomass production of transgenic plants, as indicated by augmented plant heights and shoot dry weights than the wild-type plants. All these results suggest that acid INVs play a crucial role in the internode elongation of P. heterocycla cv . pubescens and would provide valuable information for the dissection of their exact biological functions in the fast growth of bamboo.